Ethnic social capital and community development: the case of the organisation of indigenous women Masehual Siuamej Mosenyolchikauanij - Pizzio, Alex (2018)
The promotion of social capital has been set up in one of the most recurring strategies, by the governments and international agencies, in the pursuit of poverty overcoming and the diminution of the social inequalities. The purpose of this article is demonstrate, through case study, the possibilities of ethnic social capital to be set up in a social transformation tool and at the same time being a local community development mechanism. This is a study conducted with indigenous women’s organization Masehual Siuamej Mosenyolchikauanij in Cuetzalan del Progreso, Mexico. The data presented here were obtained through ethnographic records during the first semester of the year 2017. The technique of participant observation and in-depth interviews was used. It is concluded that ethnic social capital is an important resource for the development of communities in the region, as it contributes to a plural enlargement of the themes that are wrapped in development policies and projects, enables inclusion/integration of a larger contingent of social actors in local development management processes, greater inclusion/integration of subjects, diminishing inequalities in terms of social status, and widens the field of economic opportunities.